Towards targeting overactive BMP signaling in Fibrodysplasia Ossificans Progressiva - van Staalduinen, Jente; Sánchez-Duffhues, Gonzalo; ten Dijke, Peter (Student Undergraduate Research E-journal!, 2015)
Fibrodysplasia Ossificans Progressiva (FOP) is a rare monogenetic disorder in which patients develop heterotopic ossification (HO). A heterozygous mutation in BMP type I receptor ALK2 results in hyper-sensitized BMP signaling. The aim of this study is to identify small molecules which can selectively inhibit this overactive BMP pathway. Thirteen FDA-approved small molecules were tested on their effect on BMP6-induced target gene expression, alkaline phosphatase activity and mineralization in KS483 cells. We identified cryptotanshinone as a small molecule able to inhibit BMP signaling. In conclusion, cryptotanshinone could be a novel small molecule inhibitor of the overactive BMP signaling pathway in FOP.